2021
DOI: 10.1530/eje-20-1229
|View full text |Cite
|
Sign up to set email alerts
|

Recent evidence sets therapeutic targets for levothyroxine-treated patients with primary hypothyroidism based on risk of death

Abstract: Since the introduction of sensitive assays for serum thyroid-stimulating hormone (TSH) clinicians have advised hypothyroid patients to adjust the dose of levothyroxine (L-T4) in order to achieve a normal serum TSH. A minority of patients are dissatisfied with this treatment strategy and experience symptoms. Some indirect evidence suggests that a normal serum TSH may not necessarily reflect euthyroidism at the tissue level in patients treated with L-T4. Increasingly hypothyroid patients demand higher doses of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…More studies are needed to assess the effect of fT4 levels due to subclinical hypothyroidism treatment on CV events in such patients. This is crucial considering common oversubstitution and overtreatment of subclinical hypothyroidism in patients with known cardiac co-morbidities (42).…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to assess the effect of fT4 levels due to subclinical hypothyroidism treatment on CV events in such patients. This is crucial considering common oversubstitution and overtreatment of subclinical hypothyroidism in patients with known cardiac co-morbidities (42).…”
Section: Discussionmentioning
confidence: 99%
“…It makes sense not to change T4 and T3 doses simultaneously; the ETA guidelines recommend to adapt first the daily T3 dose [ 1 ]. Maintenance of a normal serum TSH level is prudent because two large independent population studies over the past 2 years have shown that mortality of hypothyroid patients treated with LT4 is increased when the serum TSH exceeds or is reduced outside the normal reference range [ 82 ]. Residual thyroid function (RTF) might be a key factor in the success of combination therapy.…”
Section: How To Make Progress In the Management Of Persistent Symptoms On Lt4 Despite A Normal Tsh?mentioning
confidence: 99%
“…Light colors indicate CIs. The distance to the final dosage dropped significantly after 2 weeks in DAT groups [goiter t ( 15 ) = 3.16, p = 0.003, cancer t ( 27 ) = 3.52, p = 0.001], but not in controls (n.s.). ( C ) Violin plots showing time to achieve TSH targets (black dots for individual patients).…”
Section: Resultsmentioning
confidence: 96%
“…After 2 weeks, clinicians made significant adjustments toward the “correct” final dosage for patients with DAT [ t (65) = 3.31, p = 0.002], but not for controls [ t (65) = 1.00, p = 0.32]. Subgroup analysis revealed that the effect of DAT was present in both goiter [ t ( 15 ) = 3.16, p = 0.006] and cancer [ t ( 27 ) = 3.52, p = 0.002] groups. The results from control groups indicate that the experienced clinicians were not able to make significant dose adjustments based on the TSH and fT4 values from the first two weeks without assistance of the DAT.…”
Section: Resultsmentioning
confidence: 99%